Mechanical design handbook (McGraw-Hill, 1996)
Streamlined and geared toward the engineering design practitioner, this text spans the range of mechanical design, from practical standard tables to classical analytic methods. It includes data relating to fabrication, function, stability, speed, reliability and performance.